Deregulation of Ion Channel and Transporter Encoding Genes in Pediatric Gliomas - Masselli, Marika; Laise, Pasquale; Tonini, Giulia; Fanelli, Duccio; Pillozzi, Serena; Cetica, Valentina; Da Ros, Martina; Sardi, Iacopo; Buccoliero, Anna Maria; Aricò, Maurizio; Genitori, Lorenzo; Becchetti, Andrea; et al. (Frontiers in Oncology, 2012)
Brain tumours, including the majority gliomas, are the leading cause of cancer-related death in children. World Health Organization (WHO) has divided paediatric brain tumours into different grades and, based upon cDNA microarray data identifying gene expression profiles (GEPs), it has become evident in the last decade that the various grades involve different types of genetic alterations. However, it is not known whether ion channel and transporter genes, intimately involved in brain functioning, are associated with such GEPs. We determined the GEPs in an available cohort of ten paediatric brain tumours initially by comparing the data obtained from four primary tumour samples and corresponding short-term cultures. The correspondence between the two types of samples was statistically significant. We then performed bioinformatic analyses on those samples (a total of nine) which corresponded to tumors of glial origin, either tissues or cell cultures, depending on the best “RNA integrity number” (RIN). We used R software to evaluate the genes which were differentially expressed (DE) in gliomas compared with normal brain. Applying a p-value below 0.01 and fold change = 4, led to identification of 2284 DE genes. Through a Functional Annotation Analysis (FAA) using the NIH-DAVID software, the DE genes turned out to be associated mainly with: immune/inflammatory response, cell proliferation and survival, cell adhesion and motility, neuronal phenotype and ion transport. We have shown that GEPs of paediatric brain tumours can be studied using either primary tumour samples or short-term cultures with similar results. From FAA, we concluded that, among DE genes, paediatric gliomas show a strong deregulation of genes related to ion channels and transporters.